(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
The aim of the study is identify the impact of cognitive behavioral program on the reduction of the degree of depression of an infertile woman. A 23 years-woman received a behavioral therapy program consisting of ten (10) sessions. We have used the inventory Beck Depression test before and after the therapy in order to verify the hypotheses of the study, we have compared the par-and post-test results. Our study showed the effectiveness of the cognitive behavioral therapy in reducing the degree of depression.